2006
DOI: 10.1080/10665680600790327
|View full text |Cite
|
Sign up to set email alerts
|

The Racialization of Hinduism, Islam, and Sikhism in the United States

Abstract: In this article I posit the "racialization" of religion, a process that begins when certain phenotypical features associated with a group and attached to race in popular discourse become associated with a particular religion or religions. By examining the experiences of Indian Americans-a group made up primarily of Hindus, Muslims, and Sikhs-I explore the racialization process and show how the racialization of religion exacerbates the "othering" of non-Christian religious groups. The article goes on to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 24 publications
1
62
0
1
Order By: Relevance
“…The government commission to investigate the issue of reasonable accommodation, chaired by Gérard Bouchard and Charles Taylor, conducted hearings around the province and concluded that the issue had been blown out of proportion by the media (Bouchard and Taylor 2008). In effect, Bouchard and Taylor point to the possibility that there may be problems for the integration of minorities based not on their own cultural distinctiveness but rather on what some have called the “racialization” of religious status (Joshi, 2006), that is to say, the possibility that religious minorities are stigmatized and experience discrimination based on religion, and on a perception of religious minorities as a racialized “other.”…”
Section: Race and Religion Of Immigrants As Issues In Canadamentioning
confidence: 99%
“…The government commission to investigate the issue of reasonable accommodation, chaired by Gérard Bouchard and Charles Taylor, conducted hearings around the province and concluded that the issue had been blown out of proportion by the media (Bouchard and Taylor 2008). In effect, Bouchard and Taylor point to the possibility that there may be problems for the integration of minorities based not on their own cultural distinctiveness but rather on what some have called the “racialization” of religious status (Joshi, 2006), that is to say, the possibility that religious minorities are stigmatized and experience discrimination based on religion, and on a perception of religious minorities as a racialized “other.”…”
Section: Race and Religion Of Immigrants As Issues In Canadamentioning
confidence: 99%
“…Unfortunately, media, popular culture, government officials, textbooks, and teachers are often sources of stereotypes and significant misinformation (Abu El-Haj, 2002;Douglass, 2003;Suleiman, 2001). Muslim students are frequently the targets of discrimination and violence ( Joshi, 2006;Sarroub, 2005;Wingfield, 2006) even as the Muslim population in U.S. schools continues to increase. Discussion of Islam in public schools is complicated by a misperception that equates "teaching about religion"-legitimate inclusion of religion as a topic of study-with Constitutionally prohibited "teaching religion"-the promotion or practice of a particular religious belief (Haynes, 1999;Moore, 2006).…”
mentioning
confidence: 99%
“…It's not that I stopped being a Turkish Muslim. Rather, the racialized readings of my body (based primarily upon my skin color, the absence of a veil, and a 'neutral' accent) have afforded me profound privileges in a society steeped in racism, and white Christian privilege (Said, 1978;Arat-Koc, 2005;Henry & Tator, 2005;Joshi, 2006).…”
Section: Introductionmentioning
confidence: 98%